A Content Analysis of Speaking Materials in English Textbook “My Next Words” used by Fifth Grade Elementary School - Shafira Amaliawati; Tessana Agustiningrum; Bambang Widi Pratolo (Universitas Muhammadiyah Enrekang, 2024)
The aim of this study is to find out the quality of the materials in the English textbook for the fifth grade of primary school. The analysis of speaking sections from the elementary school English textbook is the main goal of this study. It was a descriptive research study that used quantitative data from textbook assessment scores that were gathered using a textbook evaluation sheet. The sheet's framework was created using theories by Bao (2013) about the constituting aspects of a good textbook and learning resource selection. The research revealed that the textbook's speaking material was sufficient. This indicates that the textbook's speaking materials fall short of the requirements outlined in the framework. Based on the research findings, the researcher proposed that the textbook's speaking materials should be enhanced. As a result, the textbook's content should be taken into consideration by both ELT teachers and textbook authors in light of Dat Bao's framework for the improvement of the materials